A comparative analysis of perceived stigma among HIV-positive Ghanaian and African American males - Kwabena A Poku; J Gary Linn; Betsy L Fife; Sherry Azar; Lorna Kendrick (Taylor & Francis Group, 2005)
The purpose of this paper was to address two questions: (i) Do Ghanaian and African American males with HIV/AIDS experience different types and degrees of stigma? and (ii) Is the impact of stigma associated with HIV/AIDS on the self different for Ghanaian and African American males? A quantitative method was used, and the four dimensions of stigma (social rejection, financial insecurity, internalised shame, and social interaction) were identified and measured using combination Likert-type questionnaires. Data regarding positive feelings of selfworth and self-deprecation, stress related to body image, and personal control were also collected in Ghana and the southeastern USA. The sample consisted of 55 men from Ghana and 55 men from the southeastern USA. Results indicate that values for the scales measuring stigma and self-perception were significantly higher for the Ghanaian sample than for the African American sample. Thus we conclude that the Ghanaian sample living with HIV/AIDS experienced a greater amount of negative self-perception and stigma-related strife than the African American sample.